1984
DOI: 10.7326/0003-4819-100-4-483
|View full text |Cite
|
Sign up to set email alerts
|

Profound but Reversible Myocardial Depression in Patients with Septic Shock

Abstract: To characterize the role of cardiac function in septic shock, serial radionuclide cineangiographic and hemodynamic evaluations were done on 20 patients with documented septic shock. Although all patients had a normal or elevated cardiac index, 10 patients had moderate to severe depression of their ejection fraction with values below 0.40. Thirteen of twenty patients survived their episode. Paradoxically, 10 of 13 survivors, but none of the 7 nonsurvivors, had an initial ejection fraction less than 0.40 (p less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
678
5
41

Year Published

1985
1985
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,273 publications
(762 citation statements)
references
References 16 publications
38
678
5
41
Order By: Relevance
“…A large randomized trial and meta-analysis comparing low-dose dopamine to placebo found no difference in need for RRT, urine output, time to renal recovery, survival, ICU stay, hospital stay, or arrhythmias [282,283]. Thus, the available data do not support administration of low doses of dopamine solely to maintain renal function.…”
Section: G Vasoactive Medicationsmentioning
confidence: 99%
“…A large randomized trial and meta-analysis comparing low-dose dopamine to placebo found no difference in need for RRT, urine output, time to renal recovery, survival, ICU stay, hospital stay, or arrhythmias [282,283]. Thus, the available data do not support administration of low doses of dopamine solely to maintain renal function.…”
Section: G Vasoactive Medicationsmentioning
confidence: 99%
“…In septic shock, despite appropriate fluid resuscitation and noradrenaline administration, the following factors can create difficulty in maintaining hemodynamics: (i) difficulty in controlling peripheral vascular resistance accompanying vasodilatation (relative hypovolemic shock)119 and (ii) cardiac dysfunction associated with SIMD (cardiogenic shock) 113, 114. These pathologies can be distinguished relatively easily through echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…Both left and right ventricular dysfunction have been demonstrated in patients with sepsis using the ventricular stroke work index (SWI) [152], the depressed relationship between left ventricular SWI and CVP [119] or pulmonary artery wedge pressure (PAWP) [127,134], radionuclide blood-pool scan [153] and twodimensional echocardiography [154]. It has usually been associated with hypodynamic as opposed to hyperdynamic septic shock [119,152], and failure to survive [127,156].…”
Section: Myocardial Dysfunctionmentioning
confidence: 99%